Freestyle Soccer Training Model Based on Game For Elementary Children Aged 10-12 Years - Ade Wahyu Nor; Moch. Ali Akbar; Iwan Setiawan; Nofi Marlina Siregar (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study was to develop a game-based freestyle soccer training model for elementary school children aged 10-12 years and to find out the increase in students' interest in the game-based freestyle soccer training model for elementary school children aged 10-12 years. The method used is Research & Development with data analysis techniques used are qualitative descriptive analysis techniques and quantitative analysis techniques. This is intended to be able to reach or process all data or information so that a comprehensive explanation will be obtained. The number of samples is 20 respondents for the small test and 40 respondents for the large test. The steps taken in the research include: (1) Product design in the form of the results of a series of initial studies (2) Design validation by experts (3) Design improvement from validation results by experts (4) Limited product trials (6) Product revision (7) carry out the pre-test (8) re-test of use (9) Revise the product again (10) Implement the product after it has been repaired and is declared effective so that later the product can be applied (11) carry out the post-test. This study concludes that the game-based freestyle soccer exercise model can be applied effectively and there is an increase in student interest in the game-based freestyle soccer exercise model.